5. Creative Approaches in the Education of Students with Severe Multiple Disability - Kantor Jiří (Sciendo, 2016)
The paper presents an empirical study in the area of special education, which clarifies the function of creative techniques, their application, pupils' preferences and implementation of creative techniques in the processes of special education intervention in pupils with severe multiple disability. According to the current scientific concept, creative approaches in Czech special education are represented by various applications of artistic means in education. The methodology focus of the study is quality-based. Data collection was performed by means of interviews with 40 teachers, observations of 4 pupils during education and a content analysis of educational documents of 30 pupils. The analysis was performed by means of the embedded theory approach. The paper assesses the contribution of the study to special education in a practical context as well as delivery of artistic-oriented courses.